Recent advances in 1,8-naphthalimide-based small-molecule fluorescent probes for organelles imaging and tracking in living cells - Yu, Haitao; Guo, Yan; Zhu, Wencheng; Havener, Kaden; Zheng, Xujun (Coordination chemistry reviews, 2021)
•Small-molecule NI-based fluorescent probes for imaging and tracking organelles in living cells are systematically reviewed.•The organelle-targeting groups and possible molecular labeling mechanisms are comprehensively summarized.•A detailed introduction of NI-based fluorescent probe for monitoring these organelle dynamics, their microenvironments, bio-/chem-active species, and enzyme activities.•The challenges and perspectives of NI-based fluorescent probe in future biological applications and clinical diagnosis. The application of fluorescent probes for organelle imaging and tracking has been extensively explored in recent years due to their unique optical performance. This review focuses on 1,8-naphthalimide (NI) fluorophore highlighting the recent advances in imaging and tracking of individual or multiple organelles in living cells. Specifically, we emphasize their labeling mechanism, and summarize the applications by monitoring their dynamic microenvironment (e.g., viscosity, polarity, temperature, and pH), bioactive species (e.g., cations/anions, molecules, radicals), and the enzyme activities. We also point out the shortcomings of the reported NI-based organelle fluorescent probes and present our perspective on the future developments in this field. We hope this review can be used not only as a reference for beginners, but also as a compass of these fields, and contribute to solving more promising and meaningful topics for chemical and biological researchers.